A Study on classification of Perlis River - Siti Rawdhoh Mohd Yusof (School of Environmental Engineering, University Malaysia Perlis, 2012)
Nowadays, water pollution was viewed primarily as threat to human health. It poses serious health effect to the people as well as aquatic life. Hence, it is important to study the pollution level of river because they help to protect and know the quality of the water that is suitable for human use. This study aims to determine Water Quality Index (WQI) in Perlis River. Water samples from four samplings at three stations were sampled from January 201 until March 2012. This study involved both field and laboratory study. The laboratory tested by seven parameters which are dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), pH, total suspended solid (TSS), ammoniacal nitrogen (NH3-N) and turbidity. The quality of the river water has been classified according Department of Environment-WQI Classification and Malaysian National Water Quality Standard (NWQS). A method measured the pollutant loading is based on the activities exist. From the approach, the findings show that high pollutant loading had decreased the WQI of the river. The overall mean WQI for Station 1(Kangar City) was 58.30 and it is classified pollution whereas for Station 2(DID monitoring station) was 61.87 and can be classified as slightly polluted and overall mean WQI for Station 3(Kangar wet market) is identifying as polluted range with 41.64. The result shows that almost of the water quality parameter tested on the water samples fall down to Class II to Class IV.